Demodulators for a zero-IF Bluetooth receiver. - Samadian, S.
This paper presents low-complexity detectors for a zero-IF Bluetooth receiver based on a simple phase-domain analog-to-digital converter. Measurements and simulations prove that the detectors' sensitivity lies close to an ideal coherent Gaussian frequency-shift keying (GFSK) detector.
Keywords: ASIC; Detectors sensitivity; Direct conversion; Low-complexity detectors; Multiphase limiter discriminator; Phase encoding; Phase-domain ADC; Zero-IF Bluetooth receiver; Zero-crossing detector